1989
DOI: 10.1139/z89-137
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in thyroid hormones and osmoregulation in mature male parr and 1- and 2-year-old immature parr of Baltic salmon (Salmo salar L.)

Abstract: One-year-old Atlantic salmon improved their seawater adaptability in late spring, at a time when 2-year-old fish smoltify, though not to the same degree as the latter. One-year-old males that matured precociously were less able to adapt to seawater than immature fish. Both 1- and 2-year-old immature salmon increased their plasma levels of thyroxine when entering the smolt stage; however, both the increase and the levels were much lower in the 1-year-old fish. The seasonal patterns of plasma triiodothyronine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Secondly, the non-smolting one-year old parr also exhibited surges in insulin during the period of parr-smolt transformation, although separated in time from those of the twoyear old fish. This finding is in contrast to what has been found for thyroxine (T 4 ), where plasma levels in both one-and two-year old fish peak at the same time during smoltification, although again, levels in the non-smolting one-year old parr are significantly lower than in the two-year smolts (Rydevik et al 1989). This supports the view that T 4 plays a pivotal role in the metabolic changes which occur during parr-smolt transformation.…”
Section: Discussioncontrasting
confidence: 85%
“…Secondly, the non-smolting one-year old parr also exhibited surges in insulin during the period of parr-smolt transformation, although separated in time from those of the twoyear old fish. This finding is in contrast to what has been found for thyroxine (T 4 ), where plasma levels in both one-and two-year old fish peak at the same time during smoltification, although again, levels in the non-smolting one-year old parr are significantly lower than in the two-year smolts (Rydevik et al 1989). This supports the view that T 4 plays a pivotal role in the metabolic changes which occur during parr-smolt transformation.…”
Section: Discussioncontrasting
confidence: 85%
“…In individuals maturing for the first time, the commmencement of gonadal development is evident by mid June to early July (Jones, 1959;Mitans, 1973;Rydevik et al, 1989;Berglund, 1991). Alm (1959) showed that early sexual maturation in several salmonids is positively correlated with growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual maturation in male Atlantic salmon (Salmo salar L.) parr is a widespread phenomenon, both under natural and hatchery conditions (Jones, 1959;Osterdahl, 1969;Lundqvist, 1983). In individuals maturing for the first time, the commmencement of gonadal development is evident by mid June to early July (Jones, 1959;Mitans, 1973;Rydevik et al, 1989;Berglund, 1991). Alm (1959) showed that early sexual maturation in several salmonids is positively correlated with growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the differences in colouration between the two groups of mature fish may be associated with other endocrine changes that occur during the spring. Rydevik et al (1989) found circulating levels of thyroid hormones to be highly variable in previously mature fish during the spring. Thyroid hormones have been shown to promote changes characteristic of smolting such as silvering (Miwa & Inui, 1985).…”
Section: Discussionmentioning
confidence: 97%